Risk management of unexploded ordnance in the Republic of Serbia for environmental protection - Borovac case study - Potić, Ivan M.; Komazec, Nenad M.; Mihajlović, Ljiljana М.; Milić, Aleksandar M.; Bakrač, Saša Т. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Decades of dealing with unexploded ordnance (UXO) in some areas of the Republic of Serbia have confirmed that it presents a substantial hazard to the security of people, property, and the environment. Even though the terrain has been cleaned, various threats from difficult-to-find UXO components remain serious. Inadequate systemic solutions for UXO management can have significant harmful consequences.Methods: Based on the spatial distribution analysis and different UXO types and quantities, this article studies the effects of dangerous components of unexploded ordnance on human lives and the environment. Two different geospatial analyses were performed including the guidelines for risk management through risk elimination based on multiple criteria, the GIS, and the Remote Sensing analysis.Results: Two different geospatial analyses resulted in the areas at high risk of remaining UXO. Conclusion: The article significantly contributes to creating an environmental risk management strategy for UXO-contaminated regions. It presents an effective technique for addressing risk assessment challenges in  such sites. The analysis considers both risk analysis and environmental protection options. Using the multi-criteria analysis and the GIS, it estimates the exposure of built structures, people, soil types, and plant species to UXO dangers in key locations. This paper serves as a guideline for environmental risk assessment.
Keywords: UXO; risk management; environmental protection; security; geospatial analysis